(untitled) (World Bulletin of Public Health, 2025)
The article presents the pathomorphological and morphometric characteristics of thymus tissue in antenatal mortality of newborns. According to research results, the difference in the cellular composition of the thymus in the early and late neonatal period is a sign of the rapid development of the immune system. Using the example of morphometric measurements, it is shown that stress factors affect the thymus, cortical hyperplasia of the adrenal gland as a result of hyperproduction of cortisol, a sharp decrease in the number of cells that make up the morphofunctional structure of the thymus, and a decrease in its parameters.